AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN BANTUAN DANA OPERASIONAL SEKOLAH - Marinah Marinah; Muhammad Ruslan Abdullah; Mahadin Saleh (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This research aims to determine: 1) Implementation of accountability in the management of School Operational Assistance funds at State Elementary School 4 Malimongan, Palopo; 2) Implementation of transparency in the management of School Operational Assistance funds at the State Elementary School 4 Malimongan, Palopo. This type of research is descriptive qualitative research. Data was collected using the methods of observation, interviews, and documentation. The data analysis techniques used are data reduction techniques, data presentation, and drawing conclusions. The results of this study indicate that: 1) The application of the principle of accountability in the management of BOS funds by the State Elementary School 4 Malimongan consists of: a). The planning of BOS funds is done well, this can be seen by the existence of the RKA for one fiscal year; b) The use of BOS funds is in accordance with the technical guidelines for BOS funds which are government policies; c) Accountability by preparing financial statements as a form of accountability. With this responsibility, the school becomes a quality school and can be trusted by the community, especially the school community; d) Filing of financial statements and documents or financial data is carried out by the School Treasurer; 2) The application of the principle of transparency in the management of BOS funds by the State Elementary School 4 Malimongan consists of: a). Planning for BOS funds openly with the participation of school components, starting from the principal as the person in charge, teachers and guardians of students; b) The use ofBOS funds is carried out openly, it can be seen that in the process of preparing the accountability report, it is carried out together with the teacher; c) Accountability for BOS funds is carried out by preparing quarterly financial reports. The publication of the report is carried out by placing it on the school information board or other places that are easily accessible by the guardians of the students. In addition, the reporting process is also reported online to the government.